2021
DOI: 10.1021/acs.analchem.0c05220
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Observation of mtDNA Damage during Hepatic Ischemia-Reperfusion

Abstract: Hepatic ischemia-reperfusion (IR) injury is a severe pathophysiological event during liver surgery or transplantation and could lead to liver failure or even death. The energy supply of mitochondria plays an essential role in preventing IR injury. Mitochondrial DNA (mtDNA) is involved in maintaining the balance of energy by participating in an oxidative phosphorylation process. However, the exact relationship between IR and mtDNA remains unclear by reason of the lack of an accurate real-time analysis method. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…This result suggests that YON could replace Hochest 33258 due to stronger groove binding with DNA. According to eq , the number of binding sites ( n ) and binding constant ( K ) of YON and DNA were calculated to be 1.3 and 8.5 × 10 5 M –1 , respectively. The results confirmed that YON could sensitively and quantitatively detect DNA.…”
Section: Resultsmentioning
confidence: 99%
“…This result suggests that YON could replace Hochest 33258 due to stronger groove binding with DNA. According to eq , the number of binding sites ( n ) and binding constant ( K ) of YON and DNA were calculated to be 1.3 and 8.5 × 10 5 M –1 , respectively. The results confirmed that YON could sensitively and quantitatively detect DNA.…”
Section: Resultsmentioning
confidence: 99%
“…In the initial stage of HIRI, mitochondrial dysfunction is characterized by the opening of mPTP and subsequent CytC release, which leads to consequent hepatocyte death 34 . In addition, a decrease in TFAM, a nuclear-encoded protein that facilitates the maintenance of mtDNA integrity and prevents mutation accumulation, is a characteristic of the early phase of HIRI and further aggravates respiratory chain dysfunction, leading to mitochondrial deficiencies 10 , 35 , 36 . Under these circumstances, suppressing mPTP opening and upregulating TFAM expression in dysfunctional mitochondria is crucial in the initial stage to prevent subsequent irreparable damage.…”
Section: Discussionmentioning
confidence: 99%
“…To better characterize the molecular and 14 Oxidative Medicine and Cellular Longevity cellular events related to AKI, we used the TRAP-seq results in the GEO database to examine PLK3 expression in the translation profile of nephrons (tubules) exposed to IRI for 24 h. GO analysis showed that PLK3 was mainly involved in oxidative stress and DNA damage after renal I/R injury. DNA damage has been reported to be involved in I/R injury in a variety of vital organs, including the testicular, brain, liver, and heart [33][34][35][36]. During renal I/R injury, DNA fragmentation in the renal tubules after DNA damage occurs as early as 12 h after reperfusion and increases within 24 h [37].…”
Section: Discussionmentioning
confidence: 99%